Solitary Median Maxillary Central Incisor Syndrome: An esthetic solution in a child - Rafael de Lima Pedro; Erika Calvano Kchler; Laura Guimarães Primo; Marcelo de Castro Costa (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Solitary median maxillary central incisor syndrome (SMMCI) is a complex disorder consisting of multiple, mainly midline, defects of development resulting from unknown factors and an uncertain etiology. SMMCI tooth itself is chiefl y an esthetic problem. This case report is an esthetic resolution for a 9- year-old girl with SMMCI as suggested and diagnosed for the first time by a team of dentists. The patient presented the philtrum of her upper lip indistinct, the maxillary labial frenum absent and a single median maxillary central incisor, with symmetrical crown form. Thus, the dentist group contacted her pediatrician reporting these findings and suggesting the diagnosis of SMMCI. The proposed dental treatment was the movement of the central incisor and the right lateral incisor for a better alignment by using some mobile orthodontic appliances and recontouring this lateral tooth with composite. The esthetical finish result pleased the patient as well as her parents.